Wielkość i struktura polskiej emigracji w dobie kryzysu gospodarczego - Robak, Roksana (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
Deliberations in this paper are focused on Polish migration outflows within the space of years 2004–2008, with the main emphasis on 2008 as a year when the world recession was the most perceptible in Europe. The purpose of Author is to show kind of dissonance between expected mainly by media implications of the world economic downturn on migration and current experience supported by Polish example. The Author outlines the two major economic downturns: the 1973 oilcrisis and the Asian financial crisis in the late 1990s and their impacts on migration. Having based the study on literature and statistical data review, the author looks at a connection between current phase of crisis and quantitative change of Polish migration based on outflows to leading host countries: the United Kingdom, Germany, Ireland and the Netherlands. The data indicates that currently migration flows follow a pattern set by these world recessions, which do not conduce an occupational mobility. The article presents that the global economic slowdown has a greater impact on inhibition new inflows to European countries rather than encouraging return migration, that the predominate strategy among polish emigration is “strategy of survival” in host country. The Author also raised the worsening financial condition of Polish emigration seen from the angle of remittance flows.
Keywords: polska emigracja; światowy kryzys gospodarczy